Quantifying the Nature and Extent of Children's Real-time Exposure to Alcohol Marketing in Their Everyday Lives Using Wearable Cameras: Children's Exposure via a Range of Media in a Range of Key Places. (20th July 2018) - Chambers, Tim; Stanley, James; Signal, Louise; Pearson, Amber L; Smith, Moira; Barr, Michelle; Ni Mhurchu, Cliona
Abstract : Children wearing wearable cameras were exposed 4.5 times per day to alcohol marketing in multiple places and via a range of marketing media. The results reinforce calls for legislative restrictions and a global response to alcohol marketing in order to protect children and reduce alcohol-related harm. Abstract: Aims: Children's exposure to alcohol marketing is typically measured using self-report data, television viewing data or street marketing audits, which are subject to bias and often do not provide quantifiable measures of daily exposure. This article describes an innovative methodology to capture the world in which children live using wearable cameras. Short summary: Children wearing wearable cameras were exposed 4.5 times per day to alcohol marketing in multiple places and via a range of marketing media. The results reinforce calls for legislative restrictions and a global response to alcohol marketing in order to protect children and reduce alcohol-related harm. Methods: Children aged 11–13 years ( n = 167) wore cameras that automatically captured images approximately every 7 s for a 4-day period between June 2014 and July 2015. Content analysis of images ( n = 700, 000) was manually undertaken to assess children's exposure to alcohol marketing. Results: On average, children were exposed to alcohol marketing 4.5 (95% CI: 3.3, 6.0) times per day, excluding within off-licence retailers, on screens and product packaging. Children were exposed at home (47%), on-licence alcohol retailers (19%), off-licence shop fronts (16%) and sporting venues (12%), and via sports sponsorship (31%) and shop front signage (31%) and merchandise (25%). The highest exposure rates were found among Māori (5.4 times higher than New Zealand European) and Pacific (3.0 times higher than New Zealand European), and boys (2.0 times higher than girls). Conclusions: These findings highlight the urgent need to implement strict legislative restrictions on all forms of alcohol marketing to fulfil the World Health Organization Global Alcohol Strategy.